Life Table Parameters and Digestive Enzyme Activity of Araecerus fasciculatus (Coleoptera: Anthribidae) Feeding on Different Stored Products - Lingyan Jian; Yuping Yang; Songhai Xie; Yibin Lou; Ling Chen; Fanglian Dai; Paraskevi Agrafioti; Yu Cao; Christos G. Athanassiou; Can Li (Insects)
Araecerus fasciculatus (De Geer, 1775) is an important stored-product pest worldwide. In this study, the development time, survival rate, oviposition, and digestive enzyme (α-amylase, cellulase, pepsin, and lipase) activities of A. fasciculatus fed on five commodities (coffee, jujube, maize, wheat, and kansui) were investigated. Our results showed that the developmental duration of A. fasciculatus from egg to adult was shortest on coffee beans (51.41 days) and longest on kansui (69.65 days). The survival rate of A. fasciculatus adults was lowest on kansui (42.22%) and highest on coffee beans (63.33%). Significant differences in fecundity were also observed, with the greatest number on coffee beans (80.78 eggs/female) and the lowest on kansui (50.43 eggs/female). Araecerus fasciculatus showed the greatest intrinsic rate of natural increase (rm) on coffee beans (0.141), followed by jujube (0.129), maize (0.117), wheat (0.105), and kansui (0.097). The net productive rate (R0) showed a similar trend to rm, with values of 48.42, 42.53, 35.39, 27.53, and 21.47, respectively, on these stored products. Although no significant differences were observed in the lipase activities when A. fasciculatus was fed on different stored products, activities of α-amylase, pepsin, and cellulase were highest on coffee beans and lowest on kansui. The variation in the population development of A. fasciculatus associated with different foods may be related to its digestive enzyme performance. These results indicated that coffee beans were the most suitable host food, while kansui was the least suitable for the development of A. fasciculatus.